Konsep Keluarga Sakinah Dalam Kehidupan Bermasyarakat - Subhan, Subhan (Berasan: Journal of Islamic Civil Law, 2022)
The purpose of  this  study is to describe and analyze the  concept of family in today's social life.  This research uses a qualitative approach with the results of interviews and literature studies. The results show that the sakinah  family is a family that is fostered by a legal marriage, able to provide affection to family members so that they have a sense of security, peace and happiness.  Sakinah in the family can be understood as a state of remaining calm despite facing many obstacles and tests of life. The ideal family is one that is able to maintain peace, and has love and love.  A harmonious family or happy family is an atmosphere of harmony, harmony characterized by the presence of good agreement and cooperation between husband and wife, father, mother and parent-child. Which includes the atmosphere in the family, giving attention to each other, the existence of communication, and mutual respect between family members.